Germinación de Laurel (Laurelia sempervirens (R. et P.) Tul) y Tepa (Laurelia philippiana Looser) Obtenida en Laboratorio y Vivero - Escobar, Bernardo; Donoso, Claudio (Bosque (Valdivia), 1986)
A test of seed germination was perform e d in germinato r and nursery, with seeds of Laurelia sempervirens (R. et. P.) Tul. from Isla Teja, Valdivia, and Laurelia philippiana Looser, from two provenences, Coastal Cordillera and Andea n Cordillera of Valdivia. The best treatmen t for breaking dormanc y for Laurelia sempervirens was stratification in we t and at 4°C, for 60 days. With this treatmen t mor e tha n 75.00 0 seedlings pe r kg. of seed, maybe produce d if seeds are sown during the third week of september. The best treatmen t for th e Coastal Cordillera provenenc e of Laurelia philippiana was also stratification in we t sand at 4°C during 60 days. Fo r the Andea n Cordillera provenenc e the best treatments wer e bot h 60 and 90 days of stratification, the form e r improving germination capacity and the latter improving germination energy. Results in the nursery were rathe r poor, howeve r with tha t germination percen t it is possible to get mor e tha n 30.00 0 seedlings per kg of sown seeds.